2021
DOI: 10.3390/pharmaceutics13111942
|View full text |Cite
|
Sign up to set email alerts
|

POLRMT as a Novel Susceptibility Gene for Cardiotoxicity in Epirubicin Treatment of Breast Cancer Patients

Abstract: Anthracyclines are among the most used chemotherapeutic agents in breast cancer (BC). However their use is hampered by anthracycline-induced cardiotoxicity (AIC). The currently known clinical and genetic risk factors do not fully explain the observed inter-individual variability and only have a limited ability to predict which patients are more likely to develop this severe toxicity. To identify novel predictive genes, we conducted a two-stage genome-wide association study in epirubicin-treated BC patients. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…At the same time, RARG agonist treatment has the potential to further protect patients with or without the rs2229774 variant from cardiotoxicity [ 108 , 109 ]. POLRMT, a gene that encodes a mitochondrial DNA-directed RNA polymerase, was discovered as a novel susceptibility gene for the act of breast cancer patients in a genome-wide association study [ 110 ]. Similarly, the multiple genetic variants in the solute carrier family 28 member 3 (SLC28A3) could distinguish child patients with high or low risk for the ACT, and researchers identified the solute carrier (SLC) competitive inhibitor can effectively against ACT [ 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, RARG agonist treatment has the potential to further protect patients with or without the rs2229774 variant from cardiotoxicity [ 108 , 109 ]. POLRMT, a gene that encodes a mitochondrial DNA-directed RNA polymerase, was discovered as a novel susceptibility gene for the act of breast cancer patients in a genome-wide association study [ 110 ]. Similarly, the multiple genetic variants in the solute carrier family 28 member 3 (SLC28A3) could distinguish child patients with high or low risk for the ACT, and researchers identified the solute carrier (SLC) competitive inhibitor can effectively against ACT [ 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the genetic factors, the following are currently under investigation with potentially promising outcomes: polymorphisms in p53 (rs1042522) [ 313 , 314 ], NOS3 (rs1799983), NADPH oxidase (rs4673), GPX1 (rs1050450) [ 313 ], RARG [ 37 , 315 ], POLRMT [ 316 ] DPYD [ 317 ] and ABCC1 [ 318 ]. Interestingly, Varkoly et al, 2022 [ 319 ], demonstrated for the first time that circulating RNA virus gene sequences (e.g., influenza orthomyxovirus) were detected in the blood samples of patients with hematological malignancies or breast cancer and were associated with myocarditis and lower LVEF in response to chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Model interpretation is important for making biological discoveries from predictive models, because first-order interpretation can identify individual genes involved in a disease [22], [23] and second-order interpretation can uncover epistatic interactions among genes for a disease [24], [25]. These discoveries may provide new drug targets [26]- [28] and enable personalized formulation of treatment plans [29]- [31] for breast cancer.…”
Section: Benchmarking Of the First-order And Second-order Interpretat...mentioning
confidence: 99%